Recent record of a flat-headed cat from a rural area in Sarawak, Malaysia - Tisen, Oswald Braken; Jayasilan, Mohd. Azlan (IUCN/SSC Cat Specialist Group, 2013)
A trapped flat-headed cat was surrendered to the authorities in late 2011. This cat was held in captivity for observation, health screening, treatment of injury and habitat assessment at point of capture to determine if it was suitable for immediate release. The cat was examined and identified positive for feline panleukopenia and later died despite treatment. Here we report the cause of death and information on the locality.